The Study of the Compound Sentence Structure in the Ephemeral: Breeder - Ni Kadek Ari Dwi Safitri; Ni Putu Cahyani Putri Utami (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
Compound sentence is a combination of two independent clauses which in every clause have their own subject and verb. The aim of this research is to analyze the base structure of compound sentence used in Wattpad story entitled The Ephemeral: Breeder, and the compound sentence analyzed through a tree diagram. This study uses the observation method in collecting the data from the story. In analyzing the data, the writer uses a qualitative method to describe the base sentences in compound sentences. In this study the theory used to analyze the base sentences is the theory from Moeller (2021) about sentence structure. The other theory used is a theory proposed by Brown and Miller (1991) to classify the small unit through a tree diagram. The writer found 88 data over 13 selected chapters in the Wattpad story. Coordinating conjunction and become the most conjunction found in the compound sentences.